PATH-27. INTRAOPERATIVE ASSESSMENT OF IDH MUTATION AS A SURROGATE FOR TUMOR INFILTRATION VIA DESORPTION ELECTROSPRAY MASS SPECTROMETRY IN GLIOMAS. (14th November 2022) - Brown, Hannah; Moniz-Garcia, Diogo; Chen, Rong; Jentoft, Mark; Middlebrooks, Erik; Chaichana, Kaisorn; Quiñones-Hinojosa, Alfredo; Cooks, Robert
Abstract: BACKGROUND: Despite advances in cancer biology, surgery and its extent of resection remains the most important prognostic modulator in gliomas, with the distinction between infiltrated and non-infiltrated tissues being an issue at the penumbra. Isocitrate dehydrogenase (IDH) mutation is unique to IDH-mutant glioma cells and can be used as a potential surrogate for tumor infiltration. Here we evaluate desorption electrospray ionization-mass spectrometry (DESI-MS) as a near real-time method for detecting infiltration at the margin of IDH-mutant gliomas. METHODS: We conducted a prospective study in which DESI-MS analysis was performed on freshly obtained tissue biopsies to detect the presence of 2-Hydroxyglutarate (2HG), with subsequent review of each sample by a board-certified neuropathologist. RESULTS: A total of 247 biopsies from a 49-patient study were previously collected and analyzed at Indiana University. Assessment of IDH mutation status of 71 core biopsies yielded sensitivity, specificity, and accuracy values of 89, 100, and 94%, respectively. Subsequent improvement of the method, including the measurement of 2HG relative to an internal control (Glutamate, Glu), allowed for detection of IDH-mutant infiltration at surgical margins. We have collected 183 biopsies (116 core and 67 margin) from 23 patients. Preliminary results of IDH mutation assessments of core biopsies indicate 93% sensitivity, 100% specificity, and 98% accuracy and margin biopsies indicate 88% sensitivity, 100% specificity, and 94% accuracy. Tumor infiltration at the margin of the surgical resection by detection of IDH-mut infiltration was detected in 88% of margin biopsies from IDH mutant tumors (30 of 34 biopsies). CONCLUSION: We present a novel method to allow intraoperative evaluation of IDH mutation presence in glioma margin biopsies. Our method and its ongoing validation identified tumor infiltration beyond surgical margins and serves as a foundation for molecularly guided surgery in IDH-mut gliomas via DESI-MS.